Street Light Monitoring Using IOT - H Ravishankar Kamath, Dr; Siva Brahmaiah Rama, V; S P M Sharma B, S (International Journal of Engineering and Technology, 2018)
In the current scenario street lights are turned as an imperative ingredient. As we know plenty of electricity is squandered by street lights. So there is a necessity to rescue power as much as possible. As there exists decay in energy which is proportional to escalate the price of electricity. It is the necessity to save energy, street light monitoring system is fully automated to ameliorate the effectiveness of switching operations of street light monitoring. The Street Light Monitoring System focus is to model an astute advancement in technology by utilizing wireless technology (GSM). Each and every street light is supervised by the server based operated system which sends a information using wireless network (GSM Module) which incorporates client server solicitation which leads for effective supervision and energy economy dominance of street light monitoring system is very crucial. [1]Â Â